Independent Work of Pupils with the Textbook as Basis for Learning - Bernotas, Vytautas (Acta Paedagogica Vilnensia, 1996)
It is known that better results are achieved when pupils learn to work with textbooks and other sources of information independently. Research shows a big number of pupils do not work with the textbook in a rational way. They read textbook mechanically, without analysing the facts, making no attempts to reason rationally. The article discusses differences between work with textbook at home and in the classroom. The research was accomplished with 151 pupil of the 6th form. Their task was to analyse the textbook of physical geographic. The control work showed how the children managed to complete the task. 49,1% respondents provided correct and complete answers, 50,9% - correct, but incomplete answers. The outcomes of the research shows that on the whole pupils managed to accomplish independent work with the textbook successfully.
Keywords: School; learning methods; textbook; independent work.